Aplikasi Pengelolaan Dana ZIS Pada Lembaga Zakat, lnfaq, dan Shadaqah (Lagzis) Kota Malang - Ridwan, A. Muhtadi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2002)
This research on the application of management on zakat, infaq and shadaqah (zis) aims to understand deeply the model and mechanism of the management of zakat finance in terms of its collection, distribution and application. It specifically looks upon the system of planning, organizing, actuating, and controlling focused on the zakat, infaq, and shadaqah institution in Malang. It uses a qualitative approach by using a case study method, a study which puts the emphasis on the richness and depth of the object being studied This study is conducted in LAGZIS of Malang, an institution founded in 1999 and considered representative, credible and professional in managing the zis finance. The data of the research were collected through documentation, participatory observation, deep interview with the informants so as the researcher could get the information about the growth, progress and even future programs of development. From the result of data analysis, it is found out that as an institution, LAGZIS in Malang has met the formal prerequisite as an amil zakat, infaq and shadaqah institution with its legal authority. This institution represents itself as a modern and professional using the trustworthy principles (amanah) with Islamic missions, due to the fact that the working mechanism and also the relevant laws such as the Constitution No. 38, 1999 on the zakat management with its related rules.